Mechanical properties and failure mechanism of the polymer composite with 3-dimensionally stitched woven fabric - Lee, GW; Choi, JS; Lee, SS; Park, M; Kim, JY; Choe, CR; Lim, SH (POLYMER SOC KOREA, 2003)
The mechanical properties and failure mechanisms of through-the-thickness stitched plain weave glass fabric/polyurethane foam/epoxy composites were studied. Hybrid composites were fabricated using resin infusion process (RIP). Stitched sandwich composite increased drastically the flexural properties as compared with the unstitched fabrics. The breaking of stitching yams was observed during the flexural test and this failure mode yielded relatively high flexural properties. Composites with stitched sandwich structure improved the mechanical properties with increasing the number of stitching yams. From this study, it was concluded that proper combination of stitching density and types of stitching fiber is important factor for through-the-thickness stitched composite panels.
Keywords: MODE-I DELAMINATION; BEHAVIOR; ARCHITECTURE; COMPRESSION; FLOW